″Implementation of Provisions of the Law of Ukraine «On Education» in Educators’ Professional Development: Patterns and Arrangements″ - Lunyachek, V. Е. (Problems of Engineer-Pedagogical Education, 2018)
The paper represents patterns and arrangements for professional development of educators and managers in education within the framework of the Law of Ukraine «On Education». The researcher suggests new documentation forms for planning and recording the outcomes of educators’ professional development as well as for financial accounting and also offers to introduce an educator’s record book, etc. The renewed arrangement procedure for professional development should also incorporate launching a state portal for accumulating relevant information and a state database. The paper highlights the urgency of modernization and fundamental renovation of professional development. The author suggests implementing transfer of educational techniques as an element of professional development which will ensure more efficient application of the results obtained while carrying out Ph.D. or post-doctoral research in Education. The paper emphasizes the need for changing educators’ mentality concerning their attitude to their professional development in the new paradigm.